Carbon‐Supported Single‐Atom Catalysts: Carbon‐Supported Single Metal Site Catalysts for Electrochemical CO2 Reduction to CO and Beyond (Small 16/2021). Issue 16 (21st April 2021) - Zhu, Yuanzhi; Yang, Xiaoxuan; Peng, Cheng; Priest, Cameron; Mei, Yi; Wu, Gang
Abstract : The carbon‐supported single metal site catalysts have great potential for electrochemical CO2 reduction due to their flexibility to regulate metal centers, coordination environments, and local structures for enhancing catalytic activity and selectivity. Yi Mei, Gang Wu, and co‐workers report that besides the high efficiency of CO2 to CO conversion, single metal sites could provide a synergy to design composite catalysts for producing other C2 products (article number 2005148 ).